2010
DOI: 10.1038/jp.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

Nasal respiratory support through the nares: its time has come

Abstract: Respiratory distress syndrome (RDS) is the most common respiratory morbidity in preterm infants. Surfactant therapy and invasive mechanical ventilation through the endotracheal tube (ETT) have been the cornerstones in RDS management. Despite improvements in the provision of mechanical ventilation, bronchopulmonary dysplasia (BPD), a multifactorial disease in which invasive mechanical ventilation is a known contributory factor, remains an important cause of morbidity among preterm infants. Barotrauma, volutraum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
(38 reference statements)
0
29
0
7
Order By: Relevance
“…There has been a recent unprecedented development of nasal respiratory support for neonates in an attempt to prevent bronchopulmonary dysplasia and cerebral palsy, both of which have been associated with the use and duration of endotracheal intubation and ventilation in neonates [1], [2]. Hence, nasal continuous positive airway pressure (nCPAP) and various nasal intermittent positive pressure ventilation modalities are currently being used and tested for their relative advantages [3].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a recent unprecedented development of nasal respiratory support for neonates in an attempt to prevent bronchopulmonary dysplasia and cerebral palsy, both of which have been associated with the use and duration of endotracheal intubation and ventilation in neonates [1], [2]. Hence, nasal continuous positive airway pressure (nCPAP) and various nasal intermittent positive pressure ventilation modalities are currently being used and tested for their relative advantages [3].…”
Section: Introductionmentioning
confidence: 99%
“…23 Other pediatric investigators found that NCPAP improved effort of breathing more than bi-level positive pressure in a cohort of children with UAO, largely because of asynchrony with the bi-level support. 24 Moreover, a recently published pediatric study showed improvements in electrical activity of the diaphragm as a surrogate for effort of breathing when better synchrony is achieved on NRS.…”
Section: Discussionmentioning
confidence: 97%
“…25,26 There is also a move toward the use of modified RAM to deliver NCPAP and NIPPV. 27,28 However, to date, there is little clinical evidence of its physiological and clinical impact when delivering NIPPV. Further research is needed to understand the mechanics as well as clinical impact of such interfaces before their routine use for NIPPV can be recommended.…”
Section: Discussionmentioning
confidence: 99%